2012
DOI: 10.1159/000345636
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Suprasellar Arachnoid Cyst: Case Report and Review of the Literature

Abstract: Purpose: We present a case of a 4-year-old child who was incidentally found to have a suprasellar arachnoid cyst (SAC) after initial CT imaging at 6 weeks of age but who demonstrated no anomalies. This is only the sixth case of intracranial de novo ACs documented in the English literature and only the second case of SAC to arise de novo. Methods: Case review after an SAC was found on an MRI scan at 4 years of age which had not been present on a previous CT of the head. Results: Apparent de novo SAC formation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
(49 reference statements)
0
5
0
2
Order By: Relevance
“…1,8,9 In a few studies in English literature, there were reported subjects with prior normal CT brain imaging presenting later with a de novo suprasellar arachnoid cyst. 7,10 The long-term behavior of the cyst is variable as there are reported cases of arachnoid cysts that become larger or smaller, and, in some cases, it resolves spontaneously. 1,11,12 Symptomatic arachnoid cysts can be surgically treated with endoscopic fenestration, craniotomy for fenestration, or shunt placement, but these surgeries are associated with potential morbidities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,8,9 In a few studies in English literature, there were reported subjects with prior normal CT brain imaging presenting later with a de novo suprasellar arachnoid cyst. 7,10 The long-term behavior of the cyst is variable as there are reported cases of arachnoid cysts that become larger or smaller, and, in some cases, it resolves spontaneously. 1,11,12 Symptomatic arachnoid cysts can be surgically treated with endoscopic fenestration, craniotomy for fenestration, or shunt placement, but these surgeries are associated with potential morbidities.…”
Section: Discussionmentioning
confidence: 99%
“… 1 8 9 In a few studies in English literature, there were reported subjects with prior normal CT brain imaging presenting later with a de novo suprasellar arachnoid cyst. 7 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors showed that the individuals included in their study with or without arachnoid cysts had the same frequency of headache , dizziness, cerebral traumatic events, cognitive impairment and cognitive and depressive symptoms [14] Arachnoid cysts of the posterior temporal fossa are associated with partial temporal lobe agenesis and now there are argues if the temporal lobe agenesis is responsible for the cyst formation or if the agenesis is the consequence of the cyst formation [9] There are rare situation with de novo cyst formation [7] 6. Dismantling the arguments against Arachnoid cysts are representing just 1% from space occupying formations and a part of them ¼-1/3 are located in the posterior cerebral fossa, and is the second location after the middle cranial fossa [3] The most frequent location in children is the sylvian fissure and the middle cerebral fossa.…”
Section: Arguments To Argue the Thesismentioning
confidence: 99%
“…Arachnoid cysts are believed to exemplify a congenital abnormality which arises from splitting or duplication of the arachnoid layer of the meninges during embryonic development [1,2]. However, secondary intracranial arachnoid cysts have been reported to develop de novo [3,4] or can be related to head trauma, [5] infection, [6] and intraventricular haemorrhage of prematurity [7].…”
Section: Introductionmentioning
confidence: 99%